Federal Justice Statistics Program: Defendants Sentenced Under the Sentencing Reform Act, 2018 ([Verlag nicht ermittelbar], 2022)
These data contain records of criminal defendants who were sentenced pursuant to provisions of the Sentencing Reform Act (SRA) of 1984 and reported to the United States Sentencing Commission (USSC) during fiscal year 2018. It is estimated that over 90 percent of felony defendants in the federal criminal justice system are sentenced pursuant to the SRA of 1984. The data were obtained from the United States Sentencing Commission's Office of Policy Analysis' (OPA) Standardized Research Data File. The Standardized Research Data File consists of variables from the Monitoring Department's database, which is limited to those defendants whose records have been furnished to the USSC by United States district courts and United States magistrates, as well as variables created by the OPA specifically for research purposes. The data include variables from the Judgement and Conviction (J and C) order submitted by the court, background and guideline information collected from the Presentencing Report (PSR), and the report on sentencing hearing in the Statement of Reasons (SOR). These data contain detailed information such as the guideline base offense level, offense level adjustments, criminal history, departure status, statement of reasons given for departure, and basic demographic information. These data are the primary analysis file and include only statute, guideline computation, and adjustment variables for the most serious offense of conviction. These data are part of a series designed by Abt and the Bureau of Justice Statistics. Data and documentation were prepared by Abt.